Analisis Performa Pompa Air DAB Tipe DB-125b Sebagai Turbin Dengan Variasi Head Dinamik - Nabuasa, Meinase K; Koehuan, Verdy A.; Nurhayati, Nurhayati; Jafri, Muhamad (Universitas Nusa Cendana, 2022)
The research was conducted through experiments on pumps that functioned as turbines in this study, namely regenerative pumps or peripheral pumps, namely the DAB water pump type DB-125B. Peripheral pump is a centrifugal pump whose impeller has radial blades in bulk of 41 blades. The performance or performance of the PAT system for regenerative pumps or peripheral pumps, namely the DAB type DB-125B water pump as a hydroelectric power plant, was analyzed with variations in flow rates of 35 ltr/min, 40 ltr/min, and 45 ltr/min. The performance or performance of the PAT system of regenerative pumps or peripheral pumps, namely the DAB type DB-125B water pump as a small-scale hydroelectric power plant from experimental results with variations in flow rate shows a maximum shaft power of 5.849 W with an initial discharge at no-load of 40ltr/min. The addition of water power can directly increase the rotation of the PAT shaft, as well as with the addition of the flow rate at the head, the rotation of the turbine rotor also increases. While the addition of the flow rate, the maximum output power and PAT efficiency tend to occur at higher rotations than at low flow rates. The efficiency of PAT in this flow discharge variation reaches its maximum value at turbine rotation of 850.3 rpm of 17.39%, followed by variations of flow rate of 45 ltr/min and 35 ltr/min, each of which is 11.14% at 566.3 rpm and 8.74% at 1440.7 rpm.